Natural Nanoparticles: A Safe Bullet for Treatment and Detection of Solid Tumors - Serena Mazzucchelli (MDPI AG, 2022)
In the last couple of decades, nanoparticles have been extensively studied as carriers for cancer imaging agents and as drug delivery platforms, due to their ability to positively affect the distribution and tumor-targeting properties of delivered compounds [...]